Accountant Competency As A Moderation of The Determination of The Quality of Financial Reports With Regional Independence - Ningsih, Santy Rahayu; Suratno; Syam, Ardiansyah (LPPM Universitas Terbuka, 2025)
This study aims to examine the effect of Local Original Revenue (PAD), Balancing Funds, and Other Legitimate Local Revenues on the Financial Independence of Local Governments with Accountant Competence as a moderating variable. This study uses a quantitative approach with secondary data from local government financial reports in West Java Province during the 2014-2019 period. The analysis was carried out through a moderation regression test to measure the interaction between independent and moderating variables on financial independence. The results of the study indicate that PAD and Balancing Funds have a significant effect on the financial independence of local governments, while Other Legitimate Local Revenues show an inconsistent effect. Accountant competence plays a significant role as a moderator that strengthens the relationship between PAD and financial independence. However, the moderation effect on Balancing Funds and Other Legitimate Local Revenues is not significant. This finding emphasizes the importance of strengthening accountant competence in regional financial management to increase fiscal autonomy. The practical implication of this study is the need to increase the capacity of government accountants through relevant training and certification. This study also provides theoretical contributions in integrating stakeholder perspectives and entity theory in the analysis of local government financial independence. This study suggests further studies by including other variables such as the level of regional innovation and regional spending efficiency to broaden insights into the determinants of financial independence.